Push-out bond strength of glass fiber posts luted with two resin cements - Léon, Blanca Liliana Torres; Franco, Vitor Lopes; Silva, Emily Vivianne Freitas; Muniz, Leonardo; Ribeiro, Fernando Carneiro (Brazilian Dental Science, 2017)
Objective. To evaluate the bond strength of a prefabricated glass fiber post to the root dentin with two resin cements using the push-out test. Material and Methods. Thirty fiber posts (White Post ECD) were cemented in human endodontically treated anterior teeth with two resin cements (n=15): RelyxTM ARC and AllCem. The roots were transversely sectioned and divided in cervical, middle and apical thirds after 48 h of cementation. The specimens' retention was tested by push-out method. The results were analyzed by 2-way ANOVA and Tukey’s test (p